Endogenous technological change and interest rate in the dynamics of globalization - Firmenich, Mario Eduardo (2018)
Global economic growth has been understood in recent decades from the neoclassical perspective of the New Growth Theory, which has a seminal support in Romer (1990). In this paper, firstly, the Romer model (1990) is analyzed and it is proved that some neoclassical assumptions generate mathematical inconsistencies.   Secondly, to avoid self-contradictory results, the questioned assumptions are replaced by non-neoclassical theoretical definitions and concepts, which implies constructing a new transformed model. In addition, some stylized facts of globalization are defined and the explanatory capacity of the transformed model is tested, by interpreting such facts with this new perspective.   The conclusion is that the explanatory capacity improves if the theoretical model has the following properties: a) there is no endogenous return to balanced growth, b) there is no global automatic convergence in per capita income; c) money and interest rate, defined in fiduciary monetary units, are managed politically; d) temporary preferences depend on expectations about the future; and e) financial globalization is not a competitive market.